Juridical Review of the Problems of Constitutional Court Decision Number 90/PUU-XXI/2023 - Putri, Rusmauliana; Nuril Khasyi'in (Fakultas Syariah UIN Antasari, 2023)
Abstract: Indonesia is a country that establishes law as the basis for the principles of nation and state life in accordance with the 1945 Constitution. This article reviews the Constitutional Court decision Number 90/PUU-XXI/2023 which contains a material review of the age provisions for Presidential and Vice Presidential candidates Article 169 Letter q of the Law Number 7 of 2017 concerning General Elections regarding laws regulated in the review of statutory regulations. This research uses a normative juridical approach through library research with literature and legal documents. The results of this research reveal that the Constitutional Court as a judicial institution whose authority is stated in the Constitution, especially in examining the constitutionality of laws and regulations against the Constitution, has caused problems and controversy in decision Number 90/PUU-XXI/2023. This research examines all the problems that occurred in the decision from various points of view starting from examining the limits of constitutional authority, their position as negative legislators, the code of ethics of constitutional judges, legal standing, making the composition of decisions to formal legal defects. The conclusion of this research is that with all the problems proven not to be in accordance with the established regulations, then decision Number 90/PUU-XXI/2023 is a decision that is flawed based on law. Abstrak: Indonesia adalah negara yang menetapkan hukum sebagai dasar kehidupan prinsip berbangsa dan bernegara sesuai dengan UUD 1945. Artikel ini meninjau putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 yang berisi uji materil ketentuan usia calon Presiden dan Wakil Presiden Pasal 169 Huruf q Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum terhadap hukum yang diatur dalam pengujian peraturan perundang-undangan. Penelitian ini menggunakan pendekatan yuridis normatif melalui studi pustaka dengan literatur dan dokumen hukum. Hasil penelitian ini mengungkapkan Mahkamah Konstitusi sebagai lembaga kehakiman yang wewenangnya tercantum dalam UUD, terutama dalam menguji konstitusionalitasp peraturan perundang-undangan terhadap UUD, menimbulkan problematik dan kontroversi dalam putusan Nomor 90/PUU-XXI/2023. Penelitian ini mencermati semua problematika yang terjadi pada putusan tersebut dari berbagai macam sudut pandang mulai dari telaah mengenai batasan kewenangan konstitusi, kedudukannya sebagai negative legislator, kode etik hakim konstitusi, legal standing, pengambilan komposisi putusan hingga pada cacat hukum formil. Kesimpulan penelitian ini adalah dengan semua problematika yang terbukti tidak sesuai dengan peraturan yang ditetapkan, maka putusan Nomor 90/PUU-XXI/2023 merupakan putusan yang cacat berdasarkan hukum.